2018
DOI: 10.3390/ijms19113455
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inducible CD19-CAR T Cells with a Tet-On System for Controlled Activity and Enhanced Clinical Safety

Abstract: The tetracycline regulatory system has been widely used to control the transgene expression. With this powerful tool, it might be possible to effectively control the functional activity of chimeric antigen receptor (CAR) T cells and manage the severe side effects after infusion. In this study, we developed novel inducible CD19CAR (iCAR19) T cells by incorporating a one-vector Tet-on system into the CD19CAR construct. The iCAR19 T cells showed dox-dependent cell proliferation, cytokine production, CAR expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
2
27
0
2
Order By: Relevance
“…The CAR, however, is not fully activated until binding of the targeting scFv to the tumor cell surface antigen triggers CD3ε signaling as well [345]. Similarly, there are multiple versions of a tetracycline (doxycycline)-inducible (tet-inducible) CAR, in which CAR expression is completely dependent on the presence of the tetracycline [346,347]. The tet-inducible system, however, appears to be leaky with a significant background expression level in the absence of the inducer [347].…”
Section: Chimeric Antigen Receptor (Car)-t and Nk Cellsmentioning
confidence: 99%
“…The CAR, however, is not fully activated until binding of the targeting scFv to the tumor cell surface antigen triggers CD3ε signaling as well [345]. Similarly, there are multiple versions of a tetracycline (doxycycline)-inducible (tet-inducible) CAR, in which CAR expression is completely dependent on the presence of the tetracycline [346,347]. The tet-inducible system, however, appears to be leaky with a significant background expression level in the absence of the inducer [347].…”
Section: Chimeric Antigen Receptor (Car)-t and Nk Cellsmentioning
confidence: 99%
“…It has also been suggested to regulate CARs at the transcriptional level. Several groups have shown that a drug-inducible CAR system can be generated by controlling CAR transcription using the TET-on system, allowing reversible control of CAR T cells (76)(77)(78). CAR mRNA is thus only produced in the presence of doxycycline, although some background CAR expression was observed (76).…”
Section: Tet-on Regulationmentioning
confidence: 99%
“…CAR T-cell technologies, although having considerable therapeutic potential, are also faced with severe toxicity problems (irAEs of 3-4). To reduce these, new strategies aim at introducing inducible gene switches [108,109].…”
Section: Car T-cell Therapymentioning
confidence: 99%